Constitutionalism and Constitutionalization of International Investment Law - Urioste Samanamud, Ricardo de (2015)
The article starts from the political-juridical concept of constitutionalism or constitutionalismsand asks for the implications that these concepts may have for the economic concepts of constitutionalism and constitutionalization related to international investment law. Specifically, the article asks itself if the theoretical debate relative to the political-juridical concepts of constitutionalism have any implications on the debate regarding the constitutionalization of international investment law and the problems of lack of coherence and consistency displayed by the arbitral awards of international investment law. The article concludes in answering what would be the effects of the extrapolation of said theoretical concepts over the balance of probabilities of success for States and investors in international arbitration.